2018
DOI: 10.1111/afe.12312
|View full text |Cite
|
Sign up to set email alerts
|

Presence of the invasive brown marmorated stink bug Halyomorpha halys (Stål) (Hemiptera: Pentatomidae) on home exteriors during the autumn dispersal period: Results generated by citizen scientists

Abstract: 1 The invasive brown marmorated stink bug Halyomorpha halys (Stål) is a serious nuisance pest in buildings. 2 To address how H. halys select potential overwintering sites and to predict the risk of home invasion, citizen scientists, primarily from the Mid-Atlantic region of the U.S.A., were recruited to count the number of H. halys present on the exterior of their homes during the autumn dispersal periods in 2013 and 2014. 3 Volunteers provided daily count data on numbers present on each exterior aspect of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 40 publications
1
24
1
Order By: Relevance
“…Interestingly, we also tried to measure this phenomenon using overwintering shelters (Bergh et al 2017) deployed at different elevations, but found that most shelters yielded no adults (or minimal numbers) indicating a variety of factors play an important role for H. halys when choosing a specific overwintering site within a particular location following arrival. Adults disperse to human-made structures such as homes (Malek et al 2018), alighting in greater numbers on those that are darker in color, and with exteriors comprised of natural materials such as stone and wood (Hancock et al 2019). Factors such as elevation are likely to influence these relative numbers, but how they choose to settle within a particular location after entry into a structure has not been well-studied.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, we also tried to measure this phenomenon using overwintering shelters (Bergh et al 2017) deployed at different elevations, but found that most shelters yielded no adults (or minimal numbers) indicating a variety of factors play an important role for H. halys when choosing a specific overwintering site within a particular location following arrival. Adults disperse to human-made structures such as homes (Malek et al 2018), alighting in greater numbers on those that are darker in color, and with exteriors comprised of natural materials such as stone and wood (Hancock et al 2019). Factors such as elevation are likely to influence these relative numbers, but how they choose to settle within a particular location after entry into a structure has not been well-studied.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, this insect often disperses between different habitats in pursuit of its preferred hosts, and like many hemipterans, starts its dispersal from overwintering sites to host plants in early spring [6]. Halyomorpha halys adults overwinter in concealed, sheltered locations, including beneath the bark of dead upright trees, in rocky outcroppings, and in a variety of human-made structures, especially those located in rural landscapes [5,7,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…A key unanswered question is what factors regulate the formation of the initial aggregations prior to dispersal to overwintering sites where adults tightly cluster for the winter diapause [ 17 ]. During the autumn dispersal period, H. halys chooses sites higher in elevation, as well as ones that are dry and dark [ 18 ], while preferred anthropogenic structures on which to alight during autumn dispersal include those that are composed of wood, cement or stone and those that are darker in coloration [ 19 ]. However, far less is known about the formation of H. halys aggregations within overwintering sites.…”
Section: Introductionmentioning
confidence: 99%